The role of boredom proneness and self-control in the association between anxiety and smartphone addiction among college students: a multiple mediation model - Zhang, Li; Wang, Baokai; Xu, Qi; Fu, Chang (Frontiers in Public Health, 2023)
Background Smartphone addiction has been found to be a widespread public health issue, especially among youth. Previous studies reported a significant association between anxiety and smartphone addiction, but the underlying mechanism in this relationship is unclear. The purpose of this study was to investigate the mediating roles of boredom proneness and self-control in the relationship between anxiety and smartphone addiction. Methods Self-reported measures of anxiety, boredom proneness, self-control and smartphone addiction were administered to 1,526 Chinese college students. Results Smartphone addiction scores varied between 10 and 60 with an average of 30.89 ± 10.57 points. Anxiety had a direct and positive effect on smartphone addiction (effect = 0.18, 95% CI = 0.11–0.25), and an indirect effect on smartphone addiction through boredom proneness (effect = 0.10, 95% CI = 0.06–0.15) and self-control (effect = 0.16, 95% CI = 0.13–0.20). Boredom proneness and self-control sequentially mediated the relationship between anxiety and smartphone addiction (effect = 0.12, 95% CI = 0.10–0.15). Conclusion Anxiety is positively associated with smartphone addiction, and boredom proneness and self-control are important mediators in this relationship. Strengthening self-control and mitigating boredom could prevent smartphone addiction in anxious college students.